Subcutaneous Fat Necrosis of the Newborn: A Case Report - Sultana, Jesmin; Yasmeen, Sabina; Nazme, Nure Ishrat; Md Moslem, Mir Hasan; Haque, Zaberul SM; Fatema, Nurun Nahar (Journal of Bangladesh College of Physicians and Surgeons, 2017)
We report a case of Subcutaneous Fat Necrosis (SCFN) of a newborn which is an uncommon disorder, occurs during the first year of life, and has been attributed to perinatal stress. SCFN usually has a favorable prognosis, with complete autoresolution of subcutaneous lesions within several weeks or months, but it may also be complicated by serious metabolic alterations such as hypercalcemia. J Bangladesh Coll Phys Surg 2017; 35(4): 192-195